Nas asas de Ícaro: uma análise da Pedagogia Freinet do 2º ao 5º ano do Ensino Fundamental na perspectiva da ação docente continuada - Amorim, Giovana Carla Cardoso (2007)
Célestin Freinet was one of the most memorable educators of the twentieth century. He presented some educational alternatives that had the objective of stimulating the construction of pedagogic actions to promote the social development of the student based upon a work centered on the free expression as the way to self-structure the knowledge. With a permanent proposal of research based on the enquiry-based learning, Freinet set human capacity (cognitive, social-affective, psychometrical) taking cooperation in consideration on the processes of knowledge construction. Based on this referential, this present work has the objective to show Freinet s pedagogy in a continuous teaching action from 2nd to 5th grade focusing the teacher s discourse and also the educative practice of the students of a city public school in Natal. The observed work revealed the teacher s discourse and educative experience and delineated the students development while immersed into Freinet s educational practice. By virtue of the nature and specificity of the theme that guided our research, we chose a qualitative approach to it, as a way of conducting ourselves during our investigative process. We observed and analyzed the method that was used to conduct the activities in the classroom, as well as the ways of expression that the children used through drawings, words (oral text), or through writing. We highlight, among the written texts, the individual and collective texts, and also letters and notes, which during some moments served as a base to express a diversity of languages. The results, after a analyzing the research data, point towards a teaching practice that favors the construction of a significant learning process through the grasping of the school environment, on which all these factors are based: society, knowledge acquisition, abilities, attitudes and values. This learning process also strengthens human solidarity bonds and mutual tolerance, on which the student s social life is seated.